Regional income inequality in China and Indonesia: A comparative analysis - Takahiro Akita; Kazumi Kawamura (European Regional Science Association (ERSA), 2002)
This study examines the extent and trends of regional income inequality in China and Indonesia, and performs a comparative analysis between these two countries in terms of factors determining regional income inequality. There are a number of studies that have analyzed the relationship between economic development and regional income inequality in China and Indonesia. However, most previous studies employed provincial income and population data to measure regional income inequality and were thus unable to measure inequality within provinces. In order to rectify this drawback, we will use district-level income and population data, rather than provincial data, to measure regional income inequality, and examine not only between-province inequalities but also within-province inequalities by using the two-stage nested Theil decomposition method developed by Akita (2002). China and Indonesia are still at a relatively early stage of economic development; therefore, income-enhancing economic activities tend to have concentrated in a few districts in each province to enjoy agglomeration economies. We will show that a very large regional income inequality exists among the districts of China and Indonesia. This study will also conduct a regression analysis to explore possible determinants of within-province income inequality, in which the following variables are considered: foreign direct investment, economic dualism, and migration.
Keywords: 330